ANALISIS PRODUKTIVITAS KERJA KARYAWAN PADA KF KAYRA TENUN IKAT TROSO DI JEPARA - Maulana, Muhammad Hisyam (Jurnal Manajemen dan Profesional, 2024)
Abstract: Work productivity is the consequence of an individual's achievement in carrying out assigned tasks based on talent, experience, seriousness, and time to support the organization's success. The goal of this study is to examine employee job productivity. The author employed a quantitative descriptive research method to conduct this study. Quantitative technique, in which existing hypotheses are tested to determine their truth. Literature and questionnaires were employed to acquire data. According to the findings of this study, work discipline and work environment have a negative and minor effect on work productivity. Meanwhile, at KF, training, motivation, and compensation all have a favorable and considerable impact on job productivity. Kayra Tenun's Jepara Ikat Troso Keywords: work productivity, employees